Quantification of adulterated fox-derived components in meat products by drop digital polymerase chain reaction - Hui Wang; Chen Chen; Yan Zhang; Boxu Chen; Yongyan Li; Wenshen Jia; Jia Chen; Wei Zhou (CyTA - Journal of Food)
This paper reported a novel approach to quantification of adulterated fox-derived components in meat products by drop digital polymerase chain reaction (ddPCR). By using the F2 gene as the target gene of fox, a single primer was designed to identify the adulteration that had been added either inadvertently or deliberately during the process. In this paper, the fox meat was used as the experimental materials and a relationship was established between fox mass and copy number by extracting DNA and using DNA concentration as an intermediary. The results that across the dynamic range, the relationships between meat mass and DNA concentration were nearly linear (R2 = 0.9986), as was the relationship between DNA concentration and DNA copy number (R2 = 0.9992). Based on the DNA concentration, the following formulas were developed about the relationship between fox meat mass (Mfox) and DNA copy number (C): Mfox = 0.05C + 2.7.